The Use of "Among Us" as Independent Learning Media to Assist Student's Speaking Ability - Darmawan, Randy Diego (RETAIN : Journal of Research in English Language Teaching, 2021)
Speaking ability is a productive ability in language to deliver meaning using verbal expression. Speaking ability is an essential skill and becomes one indicator of how far students know the target language. In teaching speaking, special treatment and methods are needed, which are different from teaching other skills. In this research, the researcher proves that the online game "Among Us" can be one of the learning media to help students practice their speaking ability. The method used in this research was qualitative research with a profound observation of teaching-learning activity in one of the senior high schools in Surabaya. From the observation field note from three meetings, it was found out that the teacher applied pre-teaching, whilst teaching, and post-teaching activity. The implementation of "Among Us" occurred on whilst teaching activities at the first and second meetings. The material used in this research was asking and giving information about condition, action, and activity in the past. The result found that asking and giving information about condition and activity employed the most by the students while asking and giving information about the action in the past was rarely employed. The result of student's speaking performance on the third meeting was evaluated using the speaking performance rubric. Most of the students notably achieved the target, and only a few sufficiently achieved the target. Several students performed outstandingly. From the findings, the researcher concludes that "Among Us" can be applied as independent learning media to assist students' speaking ability in asking and giving information about condition, action, and activity in the past.